2006
DOI: 10.1007/s10526-005-4240-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan and a biocontrol streptomycete on field and potato tuber bacterial communities

Abstract: Four treatments applied on potato seed tubers i.e. talc only, chitosan only, Streptomyces melanosporofaciens strain EF-76 in talc and S. melanosporofaciens strain EF-76 in chitosan were compared for their efficiency to reduce common scab incidence. As previously reported the joint application of the geldanamycin-producing S. melanosporofaciens strain EF-76 and chitosan was effective to control common scab of potato. Nevertheless, field application of S. melanosporofaciens EF-76 did not allow the selection of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 36 publications
1
31
0
1
Order By: Relevance
“…Following inoculation, microorganisms undergo a variety of processes, including growth, death, physiological adaption, gene transfer, and interactions with the indigenous microbial community (20,40). Irrespective of plastic-greenhouse cultivation periods, changes in the soil microbial community caused by the invading E. coli O157:H7 were detected in this study (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Following inoculation, microorganisms undergo a variety of processes, including growth, death, physiological adaption, gene transfer, and interactions with the indigenous microbial community (20,40). Irrespective of plastic-greenhouse cultivation periods, changes in the soil microbial community caused by the invading E. coli O157:H7 were detected in this study (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…It is a valuable and rapid tool for microbial community analysis, but it has some limitations [29,38]. For example, some of the bacteria that were isolated from the headbox machine did not show any metabolic activity on substrates contained in the Biolog EcoPlate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some of the bacteria that were isolated from the headbox machine did not show any metabolic activity on substrates contained in the Biolog EcoPlate. Prévost et al [29] have also reported that Biolog EcoPlate could not be used to determine the metabolic proWle of bacterial species such as Streptomyces spp. In this study, strains belonging to a same taxonomic genus showed the same metabolic proWle, but some genera could not be distinguished from each other by their metabolic patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial cells were extracted from 3 g of biosolid as previously described (Prévost et al 2006). Briefly, a biosolid sample was added to 100 mL of sterile sodium pyrophosphate 0.1% (w:v) for 30 min at room temperature.…”
Section: Microbial Cell Extractionmentioning
confidence: 99%